The Implementation of Crossword Puzzle Games to Improve Student Vocabulary Mastery at SMPN 3 Muara Bungo - Ralfian Djang Jaya; Diana Oktavia; Winda Trisnawati (CV. Master Literasi Indonesia, 2025)
This study aims to improve the English vocabulary mastery of VIIIth grade students of SMPN 3 Muara Bungo by using Crossword Puzzle Games as learning media and to find out whether the use of Crossword Puzzle Games can improve the student learning process during teaching and learning activities. This study also aims to provide alternative learning media that are effective, interesting, and able to motivate students in English. This research is classroom action research, which consists of two cycles, each cycle consisting of two meetings, each cycle consisting of four stages, namely planning, implementation, observation and reflection. The subjects of this research were eight grade Junior High School 3 Muara Bungo students. This research data was collected through qualitative and quantitative data analysis techniques. The results of this research show the implementation of the use of Crossword Puzzle Games and learning outcomes (improvement) English vocabulary at eight grade of Junior High School 3 Muara Bungo. Details of teacher observation results in cycle I with an average of 86.66% in the very good category and in cycle II it was 93.33% in the excellent category. The results of student observations in cycle I were 65% in the sufficient category and in cycle II 85% in the good category. Student learning outcomes in cycle I were 60% sufficient criteria and in cycle II 80% were good/very good criteria (completed). It was concluded that using the Crossword Puzzle Game could increase students' vocabulary